Optimisation of remotely-pumped Er3+-doped fibre amplifier location in repeaterless transmission systems - NAJI, A; ZAINALABIDIN, M; ALMANSOORI, M; MAHAMDADIKAN, F; MAHDI, M (OPTICS COMMUNICATIONS, 2007)
In this paper, a new technique of designing repeaterless transmission links using a remotely-pumped erbium-doped fibre amplifier (R-EDFA) is discussed. The transmission losses before and after the R-EDFA are varied using variable optical attenuators and the bit error rate test is executed to monitor the performance of the repeaterless transmission systems. The optimised location of R-EDFA for the longest transmission distance can be experimentally determined by determining the threshold of bit error rate. The proposed technique is also verified in practical repeaterless transmission systems using real transmission fibres. (c) 2006 Elsevier B.V. All rights reserved.